Comprehensive coordinated frequency control of symmetrical CLLC-DC transformer in hybrid AC/DC microgrids - Huang, Jingjing (2022)
In hybrid ac/dc microgrids, a bus converter system involving the use of a high-frequency dc transformer (DCT) plays a vital role to transmit power between dc and ac subgrids. However, the multiple control tasks and power transfer mode switching of bidirectional dc/ac converter create big challenges for the systematic controller design of DCT. To address this concern, a comprehensive coordinated frequency control (CCFC) is put forward in this article for the symmetrical CLLC-DCT to adapt the complicated hybrid ac/dc microgrid operation. By establishing the mathematical model on the voltage conversion gain (VCG) and active power transmission ratio (APTR), four operation modes are proposed based on power transfer conditions. The corresponding operators are derived based on the circuit feature to avoid the redundant manipulations. Frequency threshold is determined to avoid both overvoltage and low-voltage issues based on the known allowable range of VCG. The proposed CCFC scheme is detailedly realized by combining both the open-loop and closed-loop schemes to facilitate the design procedure. The prototype DCT demonstrates the proposed CCFC scheme can achieve a peak efficiency of 98.2% and satisfied performances on both VCG and APTR.